2017
DOI: 10.3892/ijo.2017.4014
|View full text |Cite
|
Sign up to set email alerts
|

Bu Fei Decoction attenuates the tumor associated macrophage stimulated proliferation, migration, invasion and immunosuppression of non-small cell lung cancer, partially via IL-10 and PD-L1 regulation

Abstract: Macrophages play a pivotal role in tumor microenvironment. Bu-Fei Decoction (BFD) is a classical formula of traditional Chinese medicine (TCM) to alleviate lung cancer related symptoms, whether it has antitumor effect or could influence cancer microenvironment deserves further study. The aim of the present study was to examine the antitumor effect of BFD on non-small cell lung cancer (NSCLC), and to investigate the underlying mechanisms through tumor associated macrophages (TAMs). M2-polarized TAMs were induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 46 publications
3
60
0
Order By: Relevance
“…Upon on those findings, we hypothesize that autocrine VEGF operation by transient activation of monocytes/macrophages highly depends on the soluble factors, including IFN‐γ, IL‐10 and the proportion of proinflammatory cytokines in the milieu. In combination with our finding and the evidence demonstrated that elevated PD‐L1 expression on TAM can be inhibited by anti‐IL‐10 antibody, therefore, the PD‐L1 expression on TAM regulated by autocrine VEGF potentially existed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Upon on those findings, we hypothesize that autocrine VEGF operation by transient activation of monocytes/macrophages highly depends on the soluble factors, including IFN‐γ, IL‐10 and the proportion of proinflammatory cytokines in the milieu. In combination with our finding and the evidence demonstrated that elevated PD‐L1 expression on TAM can be inhibited by anti‐IL‐10 antibody, therefore, the PD‐L1 expression on TAM regulated by autocrine VEGF potentially existed.…”
Section: Discussionsupporting
confidence: 86%
“…In combination with our finding and the evidence demonstrated that elevated PD-L1 expression on TAM can be inhibited by anti-IL-10 antibody, 34 therefore, the PD-L1 expression on TAM regulated by autocrine VEGF potentially existed.…”
Section: Corelation Of M2 Macrophages and Vegfsupporting
confidence: 87%
“…Tumor-associated macrophages (TAMs) are one of the most abundant immune cell populations in the TME [25][26][27]. TAMs might be a potential marker for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour associated macrophages (TAMs) derived from monocytes in the blood are recruited by cytokines and chemokines secreted by cancer cells to constitute a crucial element of tumour stromal cells . TAMs provide immune escape for cancer cells by expressing immunosuppressive cytokines (IL‐10) which induces T cell dysfunction and promote tumour invasion and migration by secreting extracellular matrix remodeling enzymes (MMP‐1, MMP‐3, MMP‐10) . Under the action of colony‐stimulating factor (CSF), TAMs contribute to the enhanced invasion, angiogenesis, and immunoregulation of non‐small cell lung cancer .…”
Section: Involvement Of Microenvironmental Factors In Cca Occvurrencementioning
confidence: 99%